Perceptions of Parents whose Children Dropped Out of Education for Children at The Junior High School Level in The Fishermen's Family in The Perlis Village Pangkalan Berandan Sub Distric Langkat District North Sumatera Province - Yudistira, Windi; Zulkarnain, Zulkarnain; Kusai, Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstrakThis study was aimed to find out how the perception of parents whose children dropout in junior high school. In addition, this study also focuses on determining the relationship between parents' opinions about school dropout and the characteristics of respondents in the Perlis village Pangkalan Berandan subdistrict Langkat district North Sumatra province. With the respondents no less than 32 people are parents whose children drop out.The results of this study indicate that the perception of the parents were whole parents who did not go to school to experience that good education for children. Education is important for the future of the child. Children's behavior can also be influenced by education. Children who stop schooling at an equivalent lower level usually do not think of education because they are busy to earn an income. The research results showed that the parent-perception relationship with the fishermen's character had a significant relationship with income, the number of dependent and fishery education levels. It seems that the income, the number of dependents and the level of education have a relationship with the perceptions of parents. Keywords: Education, Perception, Fishermen